A Comparative Analysis of Primary School Curricula in Indonesia and Malaysia: Kurikulum Merdeka and KSSR - Lailatul Khasanah; Dedi Hermon; Febriandi Febriandi; Deded Chandra (AL-ISHLAH: Jurnal Pendidikan, 2026)
This study investigates how the primary education curricula of Indonesia and Malaysia—Indonesia’s Kurikulum Merdeka and Malaysia’s Kurikulum Standard Sekolah Rendah (KSSR)—compare in terms of curriculum relevance, depth of learning, and alignment between objectives, pedagogy, and assessment. Primary education plays a crucial role in developing foundational competencies and shaping long-term educational outcomes, making curriculum reform a central policy priority in Southeast Asia. Using a qualitative comparative research design, the study relies exclusively on Observation, interviews, and document analysis to ensure methodological consistency. Data were drawn from official curriculum frameworks, national education policy documents, and relevant scholarly literature from both countries. The analysis examined curriculum structure, content organization, pedagogical orientation, and assessment systems to identify key similarities and differences. The findings indicate that Kurikulum Merdeka emphasizes instructional flexibility, learner-centered and interdisciplinary learning, and character education, whereas KSSR prioritizes structured progression, mastery of foundational skills, early STEM integration, and national standardization. These contrasting approaches reflect differing governance models and national priorities in balancing innovation with accountability. This study contributes to comparative curriculum research by offering a novel cross-national perspective on two major Southeast Asian curriculum reforms and highlighting the importance of contextual alignment, teacher capacity, and balanced implementation strategies for improving primary education quality and relevance.